Empathising with Bog Bodies: Seamus Heaney and the Feminine Sublime - Patrick Wright (Janeway JS, 2017)
This article makes the case that Seamus Heaney’s bog poems, in his collection North, represent the body in such a way as to evoke the sublime. Heaney's depicition of bodies presents them as a weird conflation of terror and beauty, which is, this article claims, his precise articulation of the sublime: one that is distinct from Edmund Burke’s theory. In recognition of the fact that much of the scholarly writing on North, thus far, has focused its attention on how these poems represent Heaney’s Irishness, his relationship to politics and the Troubles, his mythopoeic imagination, and so on, this article advances the critical discourse on his work, and moves the analysis towards feminist commentary and the affective dimension of the poems. In part the intention is to address an often reductive, historicist approach to reading texts, and the swift eagerness of literary critics to seize Heaney’s poems for their own political agendas. With this in mind, this article responds to recent feminist debates on Heaney, while arguing that Heaney’s sublime does not represent an ogre-like patriarchy, but rather remains respectful of its object, and works to resolve any seeming opposition to the category of the beautiful.